Occurrence and Spatial Distribution of Mikania Micrantha Kunth in the Forestry Campus Complex, Hetauda, Nepal - Ghimire, Pramod (Journal of Multidisciplinary Research Advancements, 2026)
Invasive alien plant species (IAPS) present a significant threat to biodiversity and ecosystem health in Nepal's tropical environments, particularly in areas facing extensive anthropogenic disturbances. This research assessed composition, dominance, and habitat-specific distribution of IAPS, particularly Mikania micrantha, in the vicinity of the Forestry Campus Complex (FCC) in Hetauda, central Nepal. A total of 120 quadrats were surveyed across six distinct habitat types: forest area (FA), wetland area (WA), grassland area (GA), roadside area (RA), built-up area (BA), and non-forested area (NA) using a systematic transect method. Phytosociological characteristics, relative frequency, relative density, relative abundance, and Importance Value Index (IVI), were determined to assess species dominance, and one-way ANOVA was employed to examine variation in Mikania micrantha dominance across habitats. A total of 23 IAPS from 12 different families were recorded, with Asteraceae being the most prevalent family. Mikania micrantha was found as the most ecologically dominant invasive species, showing the highest IVI (37.08%), followed by Chromolaena odorata and Lantana camara. Habitat-wise dominance analysis showed that Mikania micrantha was distributed to built-up, forested, and roadside areas, showing considerably higher dominance in built-up areas (IVI = 57.72%) than in forest and roadside areas (p